THE POSSIBILITIES OF IMPROVING THE FUNCTIONING OF THE CEREBRAL HEMISPHERES OF PRIMARY SCHOOL STUDENTS BY MEANS OF NEUROPEDAGOGY (Conferencea, 2024)
The article discusses the possibilities of improving the functioning of the cerebral hemispheres of primary school students using neuropedagogic methods. Neuropedagogy, integrating knowledge of neurophysiology and pedagogy, offers innovative approaches to learning that take into account the cognitive characteristics of children. The main focus is on methods of activating the left and right hemispheres, as well as integrative approaches aimed at the harmonious development of both hemispheres of the brain. Practical recommendations for teachers are presented, including a differentiated approach to learning, the use of ICT and the creation of a favorable educational environment. The use of these methods helps to improve the cognitive abilities of students and the formation of a harmonious personality.